2017
DOI: 10.1093/ijnp/pyx008
|View full text |Cite
|
Sign up to set email alerts
|

The Working Memory and Dorsolateral Prefrontal-Hippocampal Functional Connectivity Changes in Long-Term Survival Breast Cancer Patients Treated with Tamoxifen

Abstract: Background:Tamoxifen is the most widely used drug for treating patients with estrogen receptor-sensitive breast cancer. There is evidence that breast cancer patients treated with tamoxifen exhibit cognitive dysfunction. However, the underlying neural mechanism remains unclear. The present study aimed to investigate the neural mechanisms underlying working memory deficits in combination with functional connectivity changes in premenopausal women with breast cancer who received long-term tamoxifen treatment.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 63 publications
1
52
0
2
Order By: Relevance
“…Structure-and Connectivity-Related Hippocampal Changes or Differences in BCP Compared to HC All seven studies illustrated structure-and connectivityrelated hippocampal changes or differences compared to HC, including hippocampal volume loss (52-54, 56, 58), hippocampal deformation (58) as well as changes in bilateral hippocampal (57) and whole-brain functional connectivity (55). Reduced hippocampal volume was reported in most of the studies, referring mainly to the left hippocampus (53,54) and posterior regions (52,54).…”
Section: Synthesized Findingsmentioning
confidence: 97%
See 3 more Smart Citations
“…Structure-and Connectivity-Related Hippocampal Changes or Differences in BCP Compared to HC All seven studies illustrated structure-and connectivityrelated hippocampal changes or differences compared to HC, including hippocampal volume loss (52-54, 56, 58), hippocampal deformation (58) as well as changes in bilateral hippocampal (57) and whole-brain functional connectivity (55). Reduced hippocampal volume was reported in most of the studies, referring mainly to the left hippocampus (53,54) and posterior regions (52,54).…”
Section: Synthesized Findingsmentioning
confidence: 97%
“…In contrast to hippocampal volume reduction, hippocampal deformation (meaning specific morphological abnormalities and differences in shape compared to healthy controls) in BCP who underwent chemotherapy and endocrine therapy were mainly observed in the right hippocampus after controlling for age compared to HC (58). In addition to structural differences, two studies measured differences in functional connectivity, including whole brain functional connectivity (55) and bilateral hippocampal network connectivity (57). Thereby, Chen et al (55) found decreased functional connectivity of the Dorsolateral prefrontal cortex (DLPFC) with the right hippocampus in BCP treated with tamoxifen compared to HC.…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deterioration in multiple cognitive domains has been observed in women receiving selective estrogen receptor modulators (SERMs), such as tamoxifen (Castellon et al, 2004; Chen et al, 2017; Ganz, Petersen, Bower, & Crespi, 2016; Palmer, Trotter, Joy, & Carlson, 2008; Schilder et al, 2009, 2010). Less is known about the changes in cognitive function associated with AI therapy because few studies have focused on cognitive function with these agents.…”
mentioning
confidence: 99%